2021
DOI: 10.3396/ijic.v17.20585
|View full text |Cite
|
Sign up to set email alerts
|

Improving hand hygiene measures in low-resourced intensive care units: experience at the Kigali University Teaching Hospital in Rwanda

Abstract: Background: Proper hand hygiene (HH) practices have been shown to reduce healthcare-acquired infections. Several potential challenges in low-income countries might limit the feasibility of effective HH, including preexisting knowledge gaps and staffing. Aim: We sought to evaluate the feasibility of the implementation of effective HH practice at a teaching hospital in Rwanda. Methods: We conducted a prospective quality improvement project in the intensive care unit (ICU) at the Kigali University Teaching Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, we observed a significant increase in ABHR usage in the participating units. Other studies conducted in LMIC, including Rwanda, 19 Malawi, 20 and Vietnam 21 also found a significant improvement in HH compliance following the implementation of HH improvement interventions which involved ensuring continuous availability of ABHR and handwashing facilities. However, these interventions were multimodal, thus, the effect of individual intervention components remains uncertain.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, we observed a significant increase in ABHR usage in the participating units. Other studies conducted in LMIC, including Rwanda, 19 Malawi, 20 and Vietnam 21 also found a significant improvement in HH compliance following the implementation of HH improvement interventions which involved ensuring continuous availability of ABHR and handwashing facilities. However, these interventions were multimodal, thus, the effect of individual intervention components remains uncertain.…”
Section: Discussionmentioning
confidence: 84%
“…Few studies conducted about hygiene compliance in health care settings among healthcare providers in Rwanda, either focused on one hospital or even one department. [7,8,9,10,11,12] The current study aimed at determining the prevalence of hand hygiene compliance among health care workers and related predictors from selected departments in 26 hospitals of Rwanda.…”
Section: Introductionmentioning
confidence: 99%